2017
DOI: 10.1016/j.redox.2016.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Plant peroxisomes: A nitro-oxidative cocktail

Abstract: Although peroxisomes are very simple organelles, research on different species has provided us with an understanding of their importance in terms of cell viability. In addition to the significant role played by plant peroxisomes in the metabolism of reactive oxygen species (ROS), data gathered over the last two decades show that these organelles are an endogenous source of nitric oxide (NO) and related molecules called reactive nitrogen species (RNS). Molecules such as NO and H2O2 act as retrograde signals amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(92 citation statements)
references
References 123 publications
2
85
0
Order By: Relevance
“…). Peroxisomes are organelles in which H 2 O 2 plays an important role in numerous metabolic processes (Corpas et al ., ). Our results demonstrated that peroxisomes were numerous and large in mesophyll cells of leaves from nematode‐infected A. thaliana plants over the entire examination period, but especially at 15 dpi (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…). Peroxisomes are organelles in which H 2 O 2 plays an important role in numerous metabolic processes (Corpas et al ., ). Our results demonstrated that peroxisomes were numerous and large in mesophyll cells of leaves from nematode‐infected A. thaliana plants over the entire examination period, but especially at 15 dpi (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Reactive oxygen species play a dual role in stress response: low ROS levels initiate adaptation mechanisms (del Río et al ., ; Corpas, ; del Río and López‐Huertas, ; Corpas et al ., ; Raja et al ., ; Corpas and Barroso, ), whereas high ROS levels cause oxidative damage to cellular components, which compromise plant viability (Foyer and Noctor, ; Sharma et al ., ; Das and Roychoudhury, ; Mittler, ). In our experiments, all examined stress treatments caused a significant increase in H 2 O 2 content in quinoa leaves.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key components of the ROS scavenging system are peroxisomes, the small ubiquitous globular organelles of approximately 1 μm in diameter bounded with a single membrane (De Duve and Baudhuin, ). Peroxisomes contain an efficient ROS‐scavenging system that includes the antioxidants ascorbate and glutathione, and several antioxidant enzymes including dehydro‐ and monodehydro‐ascorbate reductase, glutathione peroxidase, glutathione reductase, ascorbate peroxidase, peroxiredoxins, superoxide dismutase and catalase (Nyathi and Baker, ; Cruz de Carvalho, ; Corpas et al ., ). Catalase was shown to play a role in scavenging hydrogen peroxide (H 2 O 2 ) under stress conditions including drought in all thus far examined plant species, including maize, sunflower and rice (Apel and Hirt, ; Cruz de Carvalho, ).…”
Section: Introductionmentioning
confidence: 97%
“…The presence of superoxide dismutase (SOD) activity was confirmed biochemically in various species (reviewed in Corpas et al, 2017), and a Cu-Zn superoxide dismutase (CSD3) was identified in multiple Arabidopsis peroxisome proteomic studies (reviewed in . The presence of superoxide dismutase (SOD) activity was confirmed biochemically in various species (reviewed in Corpas et al, 2017), and a Cu-Zn superoxide dismutase (CSD3) was identified in multiple Arabidopsis peroxisome proteomic studies (reviewed in .…”
Section: Ros and Rns Metabolismmentioning
confidence: 99%